1979
DOI: 10.1111/j.1476-5381.1979.tb13691.x
|View full text |Cite
|
Sign up to set email alerts
|

The EFFECT OF Α‐ADRENOCEPTOR ANTAGONISTS AND METIAMIDE ON CLONIDINE‐INDUCED LOCOMOTOR STIMULATION IN THE INFANT RAT

Abstract: Subcutaneous injections of clonidine (3.9 × 10−8 mol/kg to 3.9 × 10−6 mol/kg) produced forward locomotion and wall climbing in 7‐day‐old rats in a dose‐dependent manner. The effect was reduced significantly by a preceding intraperitoneal injection of phentolamine (7.9 × 10−6 mol/kg), phenoxybenzamine (7.4 × 10−6 mol/kg), yohimbine (1.3 × 10−6 mol/kg) or piperoxan (7.4 × 10−6 mol/kg). The pA2‐values of the antagonists to the clonidine‐induced locomotor hyperactivity were: 5.1 (phenoxybenzamine), 5.2 (phentolami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…USVs are increased by CLON in a dose-related fashion, and increase in frequency over a 25-min period (Kehoe and Harris 1989). Wall climbing represents one exception, as clonidine and naloxone stimulated wall climbing in this study, as reported previously in neonatal rats (Nomura and Segawa 1979). The reason that wall climbing was observed only in naloxone-pretreated pups is not clear.…”
Section: Discussionsupporting
confidence: 54%
“…USVs are increased by CLON in a dose-related fashion, and increase in frequency over a 25-min period (Kehoe and Harris 1989). Wall climbing represents one exception, as clonidine and naloxone stimulated wall climbing in this study, as reported previously in neonatal rats (Nomura and Segawa 1979). The reason that wall climbing was observed only in naloxone-pretreated pups is not clear.…”
Section: Discussionsupporting
confidence: 54%
“…).400 One reason for the apparently contradictory results might be that clonidine during early ages exerts effects dissimilar from those at adult ages. Support for this possibility is provided by reports on the effects of clonidine on motor activity in preweaning rats (Kellogg and Lundborg, 1972;Isaacson 1977, 1981;Nomura and Segawa, 1979;Nomura et al, 1980;Pappas and Walsh, 1983). In contrast to the sedative effects repeatedly observed in adult rats (Laverty and Taylor, 1969;Maj et al, 1972;Str6mbom, 1975) clonidine stimulated motor activity in rat pups up to about 14 days of age (Reinstein and Isaacson, 1977;Nomura, 1980).…”
Section: Resultsmentioning
confidence: 76%
“…Previous developmental studies on the effect of clonidine on motor activity indicated a transition of effect from a stimulating action before 14 days of age to a sedating one after that age Isaacson, 1977, 1981;Nomura and Segawa, 1979). By contrast, clonidine exerted only a uniformly excitatory action on ultra sonic crying during the whole age period from day 6 to 8.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The fact that clonidine-induced locomotor stimu lation is reduced by a preceding intraperi toneal injection of several a-adrenoceptor antagonists, suggests that clonidine induces locomotor stimulation by activating a adrenoceptors in the central nervous system of the infant rat (5). In the adult rats, a adrenoceptors which mediate clonidine induced sedation more resemble the peri pheral presynaptic a-adrenoceptors than the postsynaptic ones (6).…”
mentioning
confidence: 99%